Resilient urban waterfront a flood-adaptive port and park redevelopment of Sta. Ana Wharf, Davao City - Cura, Diona Joy M.; Nadal, Cathe Desiree S. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
Growth → Expansion → Abandonment → Decline → Revitalization
These were the typical stages that the original ports in port-cities around the world have gone through. Sta. Ana Wharf in Davao City has been at the stage of decline for many years, with underutilized facilities, cracked piers, a heavily sited shoreline, and a periphery encroached by informal settlements. Local officials and professionals have long acknowledged the need for redevelopment in the area. Throughout the past decade or so, proposals for a water park, a marina, and bay walk have been submitted in the attempt to determine the wharf’s new and improved function or role within this thriving and growing city.
This study aims to do the same: to create a proposal for the redevelopment of Sta. Ana Wharf. This study, however, approached the problem using landscape architecture as a tool for assessing the site’s social, ecological, and aesthetic values to be able to maximize these values and design a context-sensitive development.
Research into the social aspect of the site takes a look into the past, present, and the envisioned used for the site, as well as the associations and meanings rooted in the place. The ecological aspect mainly tackles the city’s vulnerability to flooding and the site’s adjacency to the sea, making it prone to sea level rise.
All of these are the basis for the design and planning of a unique and resilient mixed use waterfront development containing facilities such as marina, ferry terminal, and commercial and recreational facilities.
Vita.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Waterfronts -- Sta. Ana(Cebu City).; Waterfronts -- Developments -- Cebu City